Regularity inheritance in pseudorandom graphs. Issue 2 (29th April 2019) - Allen, Peter; Böttcher, Julia; Skokan, Jozef; Stein, Maya
Abstract : Advancing the sparse regularity method, we prove one‐sided and two‐sided regularity inheritance lemmas for subgraphs of bijumbled graphs, improving on results of Conlon, Fox, and Zhao. These inheritance lemmas also imply improved H ‐counting lemmas for subgraphs of bijumbled graphs, for some  H .